Induksi Kalus dengan BAP (Benzylaminopurin) dan IAA (Indoleacetic acid) pada Tanaman Cabai (Capsicum annuum L.) Lokal Genotipe Lotanbar Sumatera Barat - Sihotang, Saipul; Renfiyeni, Renfiyeni; Suliansyah, Irfan; Jamsari, Jamsari (Universitas Medan Area, 2019)
This study was aimed to obtain the method in the study of callus induction of in vitro. The research activities were carried out at Laboratory of Biotechnology, Faculty of Agrotechnology, Andalas University. This research used decriptive and experimental methods. One-way ANOVA analysis followed by Duncan’s test was used to determine significant differences (P ≤ 0.05). All statistical analysis were performed using the SPSS Ver. 23 statistical software package. The results showed that medium of callus induction is 4,0 mg/L BAP + 0,5 mg/L IAA with formation of callus (days), and average of callus formed, namely 4,33 days, and 9,67 callus.